2009
DOI: 10.1212/01.wnl.0000341930.35494.66
|View full text |Cite
|
Sign up to set email alerts
|

Warm and cold complex regional pain syndromes

Abstract: Our results indicate that warm and cold complex regional pain syndromes (CRPS) are associated with different clinical findings, beyond skin temperature changes. This might have implications for the understanding of CRPS pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 28 publications
5
65
0
8
Order By: Relevance
“…Defects in cold sensation can lead to conditions such as cold allodynia and cold hyperalgesia, which are clinically important symptoms in patients suffering from neuropathic pain (Maier et al, 2010), complex regional pain syndrome (Eberle et al, 2009), chemotherapy-induced allodynia (Binder et al, 2007;Attal et al, 2009), and painful bladder syndrome (Mukerji et al, 2006). Various molecular targets have been identified as candidates for signaling cold sensing, one of which is transient receptor potential (subfamily M, member 8) (TRPM8), a nonselective cation channel (McKemy et al, 2002;Peier et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Defects in cold sensation can lead to conditions such as cold allodynia and cold hyperalgesia, which are clinically important symptoms in patients suffering from neuropathic pain (Maier et al, 2010), complex regional pain syndrome (Eberle et al, 2009), chemotherapy-induced allodynia (Binder et al, 2007;Attal et al, 2009), and painful bladder syndrome (Mukerji et al, 2006). Various molecular targets have been identified as candidates for signaling cold sensing, one of which is transient receptor potential (subfamily M, member 8) (TRPM8), a nonselective cation channel (McKemy et al, 2002;Peier et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that TRPM8 can mediate the detection of cold thermal stimuli by primary afferent sensory neurons (McKemy et al, 2002;Peier et al, 2002). Studies with TRPM8 knockout mice and selective TRPM8 channel blockers have demonstrated a lack of cold sensitivity and reduced cold pain in various rodent models (Thut et al, 2003;Chung and Caterina, 2007;Colburn et al, 2007;Dhaka et al, 2007;Caspani et al, 2009;Eberle et al, 2009;Liu and Qin, 2011). In contrast, some studies have questioned the role of TRPM8 in cold detection, or proposed that other excitatory or inhibitory channels are more important to this sensory modality in vivo (Viana et al, 2002;McKemy, 2005;Madrid et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Bei etwa 70% der Patienten entwickelt sich ein "warmes" CRPS, während bis zu 30% der Patienten bereits initial ein "kaltes" CRPS entwickeln. Ein "kaltes" CRPS geht häufiger mit motorischen Störungen einher und ist eventuell mit einer schlechteren Prognose assoziiert [7]. Die früher gern angewendete Einteilung in ein "inflammatorisches", "dystrophes" und "atrophes" Stadium ist daher aus heutiger Sicht nicht mehr allgemeingültig.…”
Section: Klinische Manifestationunclassified